TDM and stabilisation of paediatric patients in liver and kidney transplantation. Issue 2 (12th March 2012) - Baudet, H.; McLin, V.; Parvex, P.; Chehade, H.; Combescure, C.; Samer, C.; Bonnabry, P.; Fonzo-Christe, C.; Posfay-Barbe, K.
Abstract : Background: Immunosuppressants must be guided by therapeutic drug monitoring (TDM) to prevent rejection. Understanding and prevention of blood level variability is essential. Purpose: To evaluate TDM practice and factors associated with stabilisation. Materials and methods: Retrospective study of paediatric patients with liver (LT; since 2007) or kidney transplant (KT; since 2002) in two university hospitals. First-month % of tacrolimus (FK) and ciclosporin (CyA) therapeutic trough levels (FK: LT 10-15 ng/mL; KT 8-12 ng/mL / CyA KT 250-350 mcg/L). 30-day survival analysis (median survival in days (d) (CI 95%)) of stabilisation (discharge from intensive care or hospital / 3 consecutive therapeutic levels) and univariate analysis of associated factors in LT with stabilisation (log-rank test). Results: 46 patients included: 27 LT, 19 KT; mean age: 2.8 ±4.0 vs. 11.9 ±6.2 years. 100% of LT patients received FK; KT: 53% FK, 47% CyA. Only 32% (LT) and 41% (KT) of FK levels, and 22% (KT) of CyA levels were in the range. Discharge from intensive care and hospital occurred significantly later for LT (8d (6;12) versus 3 d (3;5) / 28 d (25; not available) versus 11.5 d (10;15) (p<0.001)), but stabilisation of levels earlier (18 d (15;27) vs not reached, p=0.04). Compared to FK levels, CyA levels were not stabilised in KT patients after one month (not reached vs 20.5 d (10; not available), p=0.02), but no difference was seen on discharge. Living donor transplant was significantly associated with an earlier discharge from intensive care (p=0.02), age <30 years and transplant weight ≥ 291 g with a trend to earlier discharge from hospital (p=0.048; p=0.06). Metabolic disease and weight-ratio transplant/patient ≥0.03 were associated with an earlier stabilisation of FK levels (p=0.01; p=0.05). Conclusions: Variability of immunosuppressant trough levels was high in the first month after liver transplantation and in kidney patients receiving ciclosporin. Factors associated with earlier stabilisation have to be confirmed in a larger study.